2015
DOI: 10.1007/s10295-015-1614-9
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of hxk1 gene results in derepression of xylose utilization in Scheffersomyces stipitis

Abstract: A major problem in fermenting xylose in lignocellulosic substrates is the presence of glucose and mannose which inhibit xylose utilization. Previous studies showed that catabolite repression in some yeasts is associated with hexokinases and that deletion of one of these gene(s) could result in derepressed mutant strain(s). In this study, the hxk1 encoding hexokinase 1 in Scheffersomyces stipitis was disrupted. The ∆hxk1 SS6 strain retained the ability to utilize the main hexoses and pentoses commonly found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“… [3] S. stipitis Chemicals Ethanol from lignocellulosic feeds Reviewed in Ref. [21] Fumaric acid [73] Lactic acid [74] Xylitol [75] H. polymorpha Proteins Hepatitis B surface antigen (HBsAg) Insulin IFNα-2a Reviewed in Ref. [76] Hexose oxidase Phytase Chemicals Ethanol from various carbon sources Reviewed in Ref.…”
Section: Bioprocessing and Metabolic Engineering With Non-conventionamentioning
confidence: 99%
See 1 more Smart Citation
“… [3] S. stipitis Chemicals Ethanol from lignocellulosic feeds Reviewed in Ref. [21] Fumaric acid [73] Lactic acid [74] Xylitol [75] H. polymorpha Proteins Hepatitis B surface antigen (HBsAg) Insulin IFNα-2a Reviewed in Ref. [76] Hexose oxidase Phytase Chemicals Ethanol from various carbon sources Reviewed in Ref.…”
Section: Bioprocessing and Metabolic Engineering With Non-conventionamentioning
confidence: 99%
“…Single gene deletions have also been achieved through genomic integration using a selectable genetic marker. For example, a HR method was used to create a HXK1 deficient strain lacking glucose repression and a XYL2 deficient strain that produces xylitol from xylose [75] . In another example, S. stipitis was engineered to efficiently produce lactic acid through random integration of a heterologous LDH gene, with engineered strains producing up to 58 g L −1 lactate from 100 g L −1 xylose [74] .…”
Section: Bioprocessing and Metabolic Engineering With Non-conventionamentioning
confidence: 99%
“…To obtain strains of S. stipitis that can ferment simultaneously glucose and xylose, 2-deoxyglucoseresistant mutants were isolated [173]. This was also accomplished by deletion of the gene HXK1 coding for hexokinase I [26]. The last experiment could be considered as one of very few, in which a metabolic engineering approach was applied for this organism [26].…”
Section: Scheffersomyces (Pichia) Stipitismentioning
confidence: 99%
“…This was also accomplished by deletion of the gene HXK1 coding for hexokinase I [26]. The last experiment could be considered as one of very few, in which a metabolic engineering approach was applied for this organism [26]. As a rule, experiments in metabolic engineering of S. stipitis are hampered by our limited knowledge of the limiting steps of the fermentation process.…”
Section: Scheffersomyces (Pichia) Stipitismentioning
confidence: 99%
“…Previous studies have found that strains that can utilize xylose in the presence of D-glucose homologues (structurally similar to D-glucose but not metabolizable), can co-ferment Dglucose/xylose without obvious preference [20][21][22][23][24]. Adaptive laboratory evolution of strains in a medium composing of xylose and the D-glucose analog 2-deoxyglucose (hereafter abbreviated as dG)…”
Section: Introductionmentioning
confidence: 99%